OKSIDENTALISME: KONSEP PERLAWANAN TERHADAP BARAT - Noorhayati, Siti Mahmudah (Universitas Nurul Jadid, 2016)
Occidentalism is basically oriented to deal with westernization with highly intense influence not merely on our conception and culture (Eastern), but also on the freedom of Eastern human with individual faith. Hassan Hanafi, an outstanding intellectualÂ Muslim who created genial and analytical ideas, attempted to analyze and disclosure silent ideology of Western over Islam. By behalf of the Eastern people through Occidentalism, Hanafi succesffully indicate a racial and ideological conspiration behind Western academic works with the high claim of being more civilized. However, Hanafiâ€™s Occidentalism is not intended to make coup de etat over the Orientalism. For him, the simple aim of the Occidentalism is making self-freedom of the other in order to get the equilibrium between Islamic/Eastern and European/Western worlds in general.